2015
DOI: 10.1037/a0039301
|View full text |Cite
|
Sign up to set email alerts
|

Balancing effectiveness with responsiveness: Therapist satisfaction across different treatment designs in the Child STEPs randomized effectiveness trial.

Abstract: Therapist satisfaction with a treatment approach has independent dimensions, which can vary as a function of the protocol design. By virtue of being perceived as more effective than UC and more responsive than standard EBTs, the modular protocol design was also viewed as more overall satisfying than both, and secondary analysis suggested that these results were not due to mere first impressions of the protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…Past studies have suggested that therapists prefer modular EBPs that offer flexibility in delivering session content, as opposed to standard manualized treatments (Borntrager et al, 2009; Chorpita at el., 2015). In qualitative analyses for this study, although flexibility emerged as an appealing characteristic for one modular EBP, this characteristic was discussed by therapists less frequently and for fewer EBPs than structure.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have suggested that therapists prefer modular EBPs that offer flexibility in delivering session content, as opposed to standard manualized treatments (Borntrager et al, 2009; Chorpita at el., 2015). In qualitative analyses for this study, although flexibility emerged as an appealing characteristic for one modular EBP, this characteristic was discussed by therapists less frequently and for fewer EBPs than structure.…”
Section: Discussionmentioning
confidence: 99%
“…Such approaches also include training in cross-cutting Cognitive Behavioral Therapy (CBT) techniques (e.g., using standardized assessment, CBT model explanation, assigning/reviewing homework; Sburlati, Schiering, Lyneham, & Rapee, 2011) that support treatment delivery (e.g., Weisz et al, 2012). Common elements approaches allow for the aggregation and dissemination of research knowledge, facilitate more flexible training and implementation, offer greater coverage for youth, and seem to have greater appeal among community providers (Bernstein, Chorpita, Daleiden, Ebesutani, & Rosenblatt, 2015; Chorpita & Daleiden, 2009; Chorpita, et al, 2005; Chorpita et al, 2015). …”
Section: Common Elements Approachesmentioning
confidence: 99%
“…Despite the existence of evidence-based practices (EBPs) for a range of behavioral health concerns and populations (Butler, Chapman, Forman, & Beck, 2006; Chorpita et al, 2011a), uptake in practice contexts has been slower than anticipated (President's New Freedom Commission on Mental Health, 2003; Chorpita et al, 2015). Although policy makers have issued mandates, provided incentives, and devoted billions of dollars to bring EBPs to community behavioral health (CBH) in the United States (Institute of Medicine, 2001; McHugh & Barlow, 2010) and around the world (Clark, 2011; Layard, 2006), the majority of CBH services continue to have little or no relation to practices supported by empirical evidence (Zima et al, 2005; Creed, Stirman, Evans, & Beck, 2014a).…”
Section: Introductionmentioning
confidence: 99%